Pengaruh Perhatian Orang Tua Terhadap Prestasi Belajar Matematika - Nuryanti Mursalina; Huri Suhendri; Nurhayati (CV Putra Publisher, 2022)
This research is expected to be useful for the following parties: (1) For schools, namely as input material for schools that are used as research locations, in an effort to improve to improve the quality and achievement of students' mathematics learning. (2) For teachers as a consideration for teachers to improve student learning outcomes in the subjects they teach. (3) For students it can be used as a reference material in generating interest in learning, as well as methods that can improve methods that can improve student learning outcomes. (4) Subsequent research materials as reference material for further researchers discussing research topics relevant to this research.